2013
DOI: 10.1101/gad.204750.112
|View full text |Cite
|
Sign up to set email alerts
|

Lagging strand maturation factor Dna2 is a component of the replication checkpoint initiation machinery

Abstract: Initiation of the DNA replication checkpoint in yeast is mainly mediated by Mec1 protein kinase, the ortholog of human ATR, while its homolog Tel1, the ortholog of human ATM, has a minor replication checkpoint function. Checkpoint initiation requires stimulation of Mec1 kinase activity by specific activators. Saccharomyces cerevisiae Dna2, a nuclease-helicase that is essential for Okazaki fragment maturation, is employed specifically during S phase to stimulate Mec1 kinase and initiate the replication checkpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
147
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(158 citation statements)
references
References 50 publications
9
147
2
Order By: Relevance
“…It has been shown that the Mec1 kinase activity can be activated through direct protein-protein interaction with a bipartite Mec1 activation motif in the unstructured Cterminal tails of Dpb11 and Ddc1 Burgers 2008, 2009) and also through the unstructured N- terminal region of Dna2 (Kumar and Burgers 2013). Although our results show that SWI/SNF can directly activate Mec1 independently of the known Mec1 activators such as Dpb11 (Supplemental Fig.…”
Section: Regulating Mec1 Kinase Activity Through the Swi/snf Chromaticontrasting
confidence: 50%
See 2 more Smart Citations
“…It has been shown that the Mec1 kinase activity can be activated through direct protein-protein interaction with a bipartite Mec1 activation motif in the unstructured Cterminal tails of Dpb11 and Ddc1 Burgers 2008, 2009) and also through the unstructured N- terminal region of Dna2 (Kumar and Burgers 2013). Although our results show that SWI/SNF can directly activate Mec1 independently of the known Mec1 activators such as Dpb11 (Supplemental Fig.…”
Section: Regulating Mec1 Kinase Activity Through the Swi/snf Chromaticontrasting
confidence: 50%
“…A recent study identified Dna2 and Tel1 as additional factors contributing to Mec1 activation in S phase. When these known pathways are eliminated, there is still residual Sphase Rad53 activation (Kumar and Burgers 2013), suggesting that additional factors such as SWI/SNF can contribute to Mec1 activation in S phase. The multiple pathways that regulate S-phase Mec1 activation suggest that the cell requires robust and redundant checkpoint response in S phase, and multiple mechanisms must exist to ensure optimal Mec1 activation (Zou 2013).…”
Section: Swi/snf Specifically Functions In S Phase To Promote Mec1 Acmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the cells require DNA2 for repression of replicative stress. DNA2 can trigger proper intra-S-phase checkpoints, 49 prevent replication fork reversal, 50 and restart replication when forks have already undergone reversal. 51 However, in response to ICL-inducing agents, DNA2 contributes to over-resection of DNA due to an imbalanced hyperactivation of its nuclease activity in response to loss of FancD2 and/or to impairment of the replication fork stabilizer BOD1L.…”
Section: Ganetespib Carboplatin Combinationmentioning
confidence: 99%
“…The best known example is TopBP1. In addition, it was recently reported that the essential lagging strand maturation factor Dna2 is a component of the replication checkpoint machinery in yeast (29). Thus, there is growing evidence that replication and checkpoint signaling pathways are more intimately associated than previously thought.…”
Section: Discussionmentioning
confidence: 87%